2014
DOI: 10.1016/j.bmc.2013.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of orthologous l,l-diaminopimelate aminotransferases (DapL) to enzyme inhibitory antibiotic lead compounds

Abstract: L,L-Diaminopimelate aminotransferase (DapL) is an enzyme required for the biosynthesis of meso-diaminopimelate (m-DAP) and L-lysine (Lys) in some bacteria and photosynthetic organisms. m-DAP and Lys are both involved in the synthesis of peptidoglycan (PG) and protein synthesis. DapL is found in specific eubacterial and archaeal lineages, in particular in several groups of pathogenic bacteria such as Leptospira interrogans (LiDapL), the soil/water bacterium Verrucomicrobium spinosum (VsDapL) and the alga Chlamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
4
7
0
Order By: Relevance
“…LL -diaminopimelate aminotransferase is an enzyme involved in meso -diaminopimelate, a precursor of cell wall peptidoglycan and l -lysine in plants [ 51 ]. Tyrosine transaminase (also known as tyrosine aminotransferase) catalyzes the conversion of tyrosine to 4-hydroxyphenylpyruvic acid, a precursor for homogenetisic acid, plastoquinones and tocopherols, the latter of which function as radical scavengers and protect the plants against various stresses [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…LL -diaminopimelate aminotransferase is an enzyme involved in meso -diaminopimelate, a precursor of cell wall peptidoglycan and l -lysine in plants [ 51 ]. Tyrosine transaminase (also known as tyrosine aminotransferase) catalyzes the conversion of tyrosine to 4-hydroxyphenylpyruvic acid, a precursor for homogenetisic acid, plastoquinones and tocopherols, the latter of which function as radical scavengers and protect the plants against various stresses [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…For illustration, the effect of active inhibitors on DapL orthologs like Arabidopsis thaliana (AtDapL), a flowering plant, Leptospira interrogans (LiDapL), the soil/water bacterium Verrucomicrobium spinosum (VsDapL) and the alga Chlamydomonas reinhardtii (CrDapL) have been previously reported and it was found that AtDapL and LiDapL showed the same trend of inhibition for different inhibitors in study. It clearly suggests that inhibitors effective against one species may have potential of being active for other species as well ( McKinnie et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The perimembrane domain of megaline is instrumental to the internalization of IGF‐I, and interestingly, the C‐terminal region associates with a glycogen synthase kinase‐3 (GSK‐3), which acts as a key regulator of IGF‐I transport. Mutations of the regulatory site of GSK‐3 modulate IGF‐I internalization, and pharmacological inhibition of GSK‐3 at the choroid plexus increases the internalization of IGF‐I . It would be interesting to test whether GSK‐3 inhibitors can stimulate the transport of systemically injected IGF‐I across the BBB and increase the treatment efficacy of IGF‐I.…”
Section: Discussionmentioning
confidence: 99%